New diagnostic proposals in neonatal sepsis. Review article - Lobo-Salas, Yulis-Fernanda (2023)
Background: The term "neonatal sepsis" is used to define any systemic infection associated with hemodynamic changes and clinical findings that cause severe mortality and morbidity in newborns. Objective: The objective of this study is to update the new proposals of biomarkers for the diagnosis of neonatal sepsis with the aim of improving sensitivity and specificity. This includes highlighting the pros and cons of each biomarker and reviewing general aspects of the treatment and risk factors associated with this pathology. Materials and methods: A literature review was conducted in the PubMed database, including original research and review articles published between 2020 and 2021 in both Spanish and English, focusing on neonatal sepsis. The primary keywords used for the search were epidemiology, pathophysiology, diagnosis, and treatment. Results: The incidence of neonatal sepsis may vary from one country to another. While the gold standard for diagnosis remains the blood culture, its sensitivity and specificity can be enhanced when used in conjunction with other paraclinical tests and biomarkers. The World Health Organization guidelines recommend as first-line treatment the intravenous dual therapy of ampicillin with gentamicin, though this may be evaluated based on the resistance profile of each pathogen. Conclusion: Early diagnosis and appropriate treatment play a crucial role in altering the natural course of the disease and improving the prognosis of affected patients.